The Electron Structure of the Solar Wind - Borovsky, Joseph E.; Halekas, Jasper S.; Whittlesey, Phyllis L. (Frontiers in Astronomy and Space Sciences, 2021)
Time-series measurements of the number density ncore and temperature Tcore of the core-electron population of the solar wind are examined at 1 AU and at 0.13 AU using measurements from the WIND and Parker Solar Probe spacecraft, respectively. A statistical analysis of the ncore and Tcore measurements at 1 AU finds that the core-electron spatial structure of the solar wind is related to the magnetic-flux-tube structure of the solar wind; this electron structure is characterized by jumps in the values of ncore and Tcore when passing from one magnetic flux tube into the next. The same types of flux-tube jumps are seen for Tcore at 0.13 AU. Some models of the interplanetary electrical potential of the heliosphere predict that Tcore is a direct measure of the local electrical potential in the heliosphere. If so, then jumps seen in Tcore represent jumps in the electrical potential from flux tube to flux tube. This may imply that the interplanetary electrical potential (and its effect on the radial evolution away from the Sun of solar-wind ions and electrons) independently operates in each flux tube of the heliosphere.